Accessibility and Usability of Library Websites to Students with Visual and Physical Disabilities in Public Universities in Kenya - Kiruki, Beatrice Wamaitha; Mutula, Stephen Mudogo (International Journal of Knowledge Content Development & Technology, 2021)
This article examines the accessibility and usability of the library websites by students with visual and physical disabilities in universities in Kenya. The article is derived from a doctorate research study undertaken at the University of KwaZulu-Natal (South Africa) that examined how public university libraries in Kenya provided information services to students with visual and physical disabilities. The study used survey research design and adopted a mixed methods approach where data were gathered using survey questionnaire, focus group discussions, structured interviews, and observation. The study population consisted of six public universities that had a longstanding tradition of enrolling students with disabilities. Data were gathered from students with visual disabilities (86), students with physical disabilities (91). University Librarians (6), Personnel from the Disability Mainstreaming departments (5), Systems Librarians (5), and the Library Personnel who dispensed information services to students with visual and physical disabilities (133). Social Model of Disability and IFLA Access to Libraries for Persons with Disabilities checklist were used as the conceptual and theoretical framework in the study. The results revealed that all the libraries had library websites. However, the websites did not provide disability services page or any information designed for individuals with disabilities. The study also revealed a lack of awareness of the existence of library websites among some students with disabilities. Furthermore, others were unaware they could access e-resources through the library websites. The study also revealed that the website design posed various challenges to students with visual disabilities. Given this scenario, the study concluded that people with disabilities were excluded from access and use of library websites in public universities. The authors recommended that library websites must contain disability services page providing information suitable for persons with disabilities as well as create awareness of the same. The libraries should evaluate their websites to ensure compliance with W3C requirements for web content accessibility. Additionally, the libraries should develop library disability policy to give guidance on the provision of digital information as well as other information services to persons with disabilities. URL: http://ijkcdt.net/xml/29430/29430.pdf